Ivy Sign in Mildly Symptomatic β-Thalassemia Intermedia, with Development of Moyamoya Disease. Issue 1 (February 2014) - El Beltagi, Ahmed H.; El-Sheikh, Ahmed; El-Saif, Reem; Norbash, Alexander
Cerebrovascular occlusive disease with secondary proliferative angiogenesis can be idiopathic as a standalone disease state, known as moyamoya disease, or it may develop secondary to different disease entities, such as chronic hemoglobinopathies, in which case it is known as moyamoya syndrome. Although moyamoya syndrome has been well described with sickle cell anemia, its association with other hemoglobinopathies is rarely reported. We describe a 16-year-old girl with β-thalassemia intermedia who presented with recurrent headaches and focal seizures non-responsive to medical treatment. Magnetic resonance imaging showed diffuse intrasulcal bright signal intensity on fluid-attenuated inversion recovery and leptomeningeal enhancement previously termed the "ivy sign", and her magnetic resonance angiography was consistent with bilateral moyamoya disease. The literature describing and explaining the pathogenesis of the "ivy sign" and its relationship to moyamoya disease was reviewed.